2019
DOI: 10.1021/acsaelm.9b00266
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Oxidation of AlInN for III-Nitride Electronic and Optoelectronic Devices

Abstract: The oxidation of semiconductors is a fundamental building block of many modern electronic devices. The prime example is the oxidation of silicon into silicon dioxide, which is used as a gate dielectric, waveguides, masking layer, and a device isolation layer. The ability to form an analogous stable and insulating oxide in III-nitride semiconductors would enable a new generation of III-nitride-based electronic and optoelectronic devices. Here we present data on the conversion of thick (>100 nm) AlInN epitaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[1] In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells. [2][3][4][5][6][7][8] In that sense, radio-frequency (RF) magnetron sputtering allows the deposition of large-area and single-phase AlInN material using this low-cost and low-temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells. [2][3][4][5][6][7][8] In that sense, radio-frequency (RF) magnetron sputtering allows the deposition of large-area and single-phase AlInN material using this low-cost and low-temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…III‐Nitride semiconductors are interesting materials for the development of novel devices due to their direct bandgap energy tunable from the infrared (0.7 eV) for InN to the UV (6.2 eV) for AlN, their strong chemical and temperature endurance, and their radiation hardness . In particular, AlInN alloys are special candidates for power electronics, highly efficient emitters, optoelectronic devices, and solar cells . In that sense, radio‐frequency (RF) magnetron sputtering allows the deposition of large‐area and single‐phase AlInN material using this low‐cost and low‐temperature technology exportable to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations 2 of the oxidation of other Al-containing III-V semiconductors have also been carried out to gain additional chemico-physical insight and to potentially expand the use of this process to make transistors or photonics devices operating in other spectral bands than the near-infrared window (800-1000 nm). So far, the studied alloys include AlIn(Ga)P 28 on GaAs, AlInAs [29][30][31][32] and AlAsSb [33][34][35] on InP, AlInN on GaN 36,37 , and AlAsSb on GaSb [38][39][40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…In the infrared GaAs-based VCSELs, selective AlGaAs oxide layers can be facilitated by a steam oxidation, and work well as the current and optical confinements. 23) A steam oxidation of an AlInN surface has been reported, 24) but so far no such selective oxide layers have been established in GaN-based materials. Under the circumstances, in 2013, Hashemi et al theoretically showed large optical loss values (40 cm −1 ) without the optical confinement, and proposed various confinement structures with a convex step mesa and/or a surrounding buried oxide layer.…”
mentioning
confidence: 99%